The Relationship between Adolescents Bullying Role and Grandiose Narcissism - Shu, Xiaoxin. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Child Development.; Advisor: Theo Klimstra.; Keywords: Psychology, Personality psychology, and Developmental psychology.